Investigating Upper Secondary ESL Students’ Language Learning Strategies for Speaking Skills - John Peter, Anthony; Albert, Christina; Michelle Masing, Deffenie; Valerie Karim, Veronica; Hashim, Harwati (International Journal of Academic Research in Progressive Education and Development, 2023)
Speaking is a useful language skill because it allows speakers and listeners to talk to each other to share information and build long-term relationships. English is one of those languages that people from all over the world want to learn, no matter what level of communication they are at. But developing speaking skills in ESL students is always seen as hard and complicated, requiring a lot of work to keep up. This study investigated the preferred learning language strategies (LLS) used for speaking skills by Form 5 ESL students in a rural school in Sarawak. A total of 45 students with different proficiency levels were selected for this study. The questionnaire was adapted from Young Learner’s Language Strategy Use Survey and the Language Strategy Use Survey. Then, the data was analysed using the Statistical Package for Social Science (SPSS) version 26. The results revealed that students employ various speaking strategies and continuously improve their language skills to become proficient in L2. Regular practise, especially outside the classroom, improves speaking skills, besides consistent language practise which builds confidence, fluency, and accuracy.